Coding and Artificial Intelligence Learning to Improve Elementary School Students' Digital Literacy - Dewi Ni Luh Putu Manik Candra; Luh Rizka Aprilia Dewi; Ni Putu Wipradnyani Prasetya Dewi; Luh Nopiani; Putu Regina Septiani Agatha (Indonesian Journal Publisher, 2026)
The rapid advancement of digital technology has transformed the educational landscape and increased the need to strengthen digital literacy among elementary school students. In the Society 5.0 era, students are expected not only to use technology but also to understand, evaluate, and apply it responsibly. This study aims to analyze the role of coding and artificial intelligence learning in enhancing the digital literacy of elementary school students. A Systematic Literature Review method was employed by examining 11 scientific articles published between 2021 and 2026. Data were collected from various academic databases and analyzed using content analysis and thematic analysis to identify patterns, trends, and key findings related to the implementation of coding, AI, and digital literacy in elementary education. The findings indicate that coding and AI learning positively contribute to the development of students’ digital literacy, computational thinking, critical thinking, creativity, problem-solving abilities, and other essential 21st-century skills. Coding activities help students understand the fundamental logic of digital technologies, while AI-based learning supports more adaptive, interactive, and personalized learning experiences. However, several challenges remain, including limited technological infrastructure, unequal access to digital resources, and insufficient teacher competence in integrating coding and AI into classroom instruction. The study concludes that coding and AI learning have significant potential to improve elementary school students’ digital literacy and prepare them for future technological challenges. Therefore, strengthening teacher professional development, improving technological infrastructure, and developing supportive curricula are essential to ensure the effective and sustainable implementation of coding and AI education in elementary schools.